Core topics in paediatric anaesthesia - James, Ian (Ian Gordon); Walker, Isabeau (Cambridge medicine (Series), 2013)
Covers the important elements of paediatric anaesthesia in a concise, structured manner, providing invaluable information for established and aspiring practitioners.